Maximum Radiated Emissions of Printed Circuit Board Using Analytical Methods - Mohd Zarar Mohd Jenu; Ahmed M. Sayegh; Syarfa Zahirah Sapuan (Institute of Advanced Engineering and Science, 2017)
The rapid progress of technology has imposed significant challenges on Printed Circuit Boards (PCB) designers. Once of those challenges is to satisfy the electromagnetic compatibility (EMC) compliance requirements. For that reason, EMC compliance must be considered earlier at the design stage for time and cost savings. Conventionally, full wave simulation is employed to check whether the designed PCB meets EMC standards or not. However, this method is not a suitable option since it requires intensive computational time and thus increasing the unit cost. This paper describes novel analytical models for estimating the radiated emissions (RE) of PCB. These models can be used to help the circuit designer to modify their circuit based on the maximum allowable RE comparing to the relevant EMC-RE standard limit. Although there are many RE sources on PCB, this paper focuses on the significant source of RE on PCB; namely PCB-traces. The trace geometry, termination impedance, dielectric type, etc. can be specified based on the maximum allowable emissions. The proposed models were verified by comparing the results of the proposed models with both simulation and experimental results. Good agreements were obtained between the analytically computed results and simulation/measurement results with accuracy of ±3dB.